RF Precoder Design with Preselection Codebook for Millimeter Wave MIMO Systems - Yuan, Yipu; Huang, Yu-Jie; Yu, Jung-Lang (2018 IEEE International Conference on Computer and Communication Engineering Technology (CCET), 2018)
The radio frequency (RF) precoder/combiner design using phase shifter in millimeter wave (mmWave) multiple-input system is cost-efficient and realizable. The codebook-based strategy creates a set of steering vectors with quantized phase-shifter and finds the optimal RF precoder/combiner by a proper searching algorithm. However, the quantized steering vector might not have high gains to the channel. In this paper, we present the preselection codebook scheme which generates a set of shifted codebooks followed by a selection algorithm to pick the best codebook. Then the searching algorithm is applied to the picked codebook to find the optimal RF precoder/combiner. The simulation results show that the preselection codebook scheme provides a huge performance improvement over the original codebook method.